2020
DOI: 10.1111/clr.13694
|View full text |Cite
|
Sign up to set email alerts
|

The migration of neighboring and antagonist teeth three months after implant placement in healed single tooth‐missing sites

Abstract: Objectives To quantify the neighboring and antagonist teeth migration of a single posterior tooth‐missing site within 3 months using digital scanning and measuring techniques. Materials and Methods Intraoral scans (IOS) were made in 40 patients presenting a single posterior tooth‐missing gap and receiving implant therapy. IOS were obtained at the day of and three months after implant surgery rendering a digital baseline model (BM) and a digital follow‐up model (FM). Digital models were superimposed using the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Moreover, the migration rate of the distal teeth was significantly higher in the younger than 30 years old group than in the other two groups. It is similar to the result in Guo and colleagues’ study, 4 in which they detected a significantly greater mesial–distal gap reduction in the younger group. Studies showed that the younger population has higher alveolar bone turnover, 34–36 and stronger masticatory forces in the younger group may synergistically hasten tooth movement.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Moreover, the migration rate of the distal teeth was significantly higher in the younger than 30 years old group than in the other two groups. It is similar to the result in Guo and colleagues’ study, 4 in which they detected a significantly greater mesial–distal gap reduction in the younger group. Studies showed that the younger population has higher alveolar bone turnover, 34–36 and stronger masticatory forces in the younger group may synergistically hasten tooth movement.…”
Section: Discussionsupporting
confidence: 90%
“…The number of teeth lost was controlled within three in each arch to ensure the accuracy of the superimposition process. Dentition superimposition was also utilized for tooth migration measurement in Guo's study, 4 and they obtained dentition models using oral scanning, which was reported to hold a higher accuracy than CBCT, 37 but it is limited to the crown, with no information on the root, the alveolar bone, and so on; besides, an additional device and expense were required.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations